Inversions are bigger on the X chromosome. Issue 6 (29th August 2018) - Cheng, Changde; Kirkpatrick, Mark
Abstract: In many insects, X‐linked inversions fix at a higher rate and are much less polymorphic than autosomal inversions. Here, we report that in Drosophila, X‐linked inversions also capture 67% more genes. We estimated the number of genes captured through an approximate Bayesian computational analysis of gene orders in nine species of Drosophila . X‐linked inversions fixed with a significantly larger gene content. Further, X‐linked inversions of intermediate size enjoy highest fixation rate, while the fixation rate of autosomal inversions decreases with size. A less detailed analysis in Anopheles suggests a similar pattern holds in mosquitoes. We develop a population genetic model that assumes the fitness effects of inversions scale with the number of genes captured. We show that the same conditions that lead to a higher fixation rate also produce a larger size for inversions on the X.